2019
DOI: 10.1016/j.jcot.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Microfractures and hydrogel scaffolds in the treatment of osteochondral knee defects: A clinical and histological evaluation

Abstract: Background: Osteochondral knee defects (OCD) are often symptomatic, causing pain and functional impairment even in young and active patients. Regenerative surgical options, aiming to stimulate natural cartilage healing, have been recently used as a first line treatment. In this study, a new hydrogel is investigated in its capacity to regenerate the ultra-structural quality of hyaline cartilage when combined with a classical microfracture technique. Material and methods: Forty-six patients, affected by grade II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 41 publications
0
44
0
1
Order By: Relevance
“…The thin superficial zone forming the gliding surface in contact with the synovial fluid was characterized by small, flattened chondrocytes with poor matrix; deeper layers showed larger and rounder chondrocytes rounded by abundant extracellular matrix. Immunohistochemistry assay for human type II collagen confirmed the restoration of the hyaline cartilage, which was observed in the extracellular matrix of hyaline cartilage, whereas collagen type II was not detected in sub-chondral bone [8].…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The thin superficial zone forming the gliding surface in contact with the synovial fluid was characterized by small, flattened chondrocytes with poor matrix; deeper layers showed larger and rounder chondrocytes rounded by abundant extracellular matrix. Immunohistochemistry assay for human type II collagen confirmed the restoration of the hyaline cartilage, which was observed in the extracellular matrix of hyaline cartilage, whereas collagen type II was not detected in sub-chondral bone [8].…”
Section: Resultsmentioning
confidence: 74%
“…The preliminary result of the treatment of osteochodral knee defects with microfractures and injectable Polyglucosamine/Glucosamine Carbonate (PG/GC) have been recently reported. This is a hydrogel scaffold which is applied onto cartilage defect, and rapidly solidifies at body temperature providing support for Bone-Marrow (BM)-MSCs following microfracture [8]. In this study, we investigated a methodology to create a simple and reproducible cartilage repair procedure, using biomaterials to guide endogenous healing and new cartilage formation.…”
Section: Introductionmentioning
confidence: 99%
“…They reported improvement in WOMAC score of 58.6 ± 11.0 in the study group to 7.1 ± 9.2 at six months and 2.9 ± 5.9 at 24 months. They concluded that microfracture “augmentation” might improve the clinical outcomes in osteochondral defects [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, previous findings have shown that Avance ® Nerve Graft (AxoGen Inc.) has been used to repair human sciatic nerve defect and achieve positive axon regrowth and motor functional recovery ( 99 ). Besides, a biocompatible hydrogel scaffold (Geistlich Pharma AG) isolated from the decellularized and demineralized bone has confirmed promising outcomes for repairing early and mid-term clinical osteochondral knee defects ( 100 ). The common features of these ECM-P for extensive applications of regenerative medicine can be categorized as follows: i) Preserving meshwork of native architecture and biologically active molecules; ii) excellent mechanical and structural profiles; iii) biodegradation and temperature-sensitive property; and iv) easily integrating with the native tissue by filling the irregular defects.…”
Section: Application Of Ecm-p In Regenerative Medicinementioning
confidence: 99%